The Effect of Organo-Mineral Fertilizer Application on Cotton Yield and Fiber Quality - qizi, Merganova Ozodachehra Muhammad Arif; Ibragimov, O. O. (Research Parks Publishing LLC, 2022)
The article provides information on the effect of the use of organo-mineral fertilizers on the yield of cotton and fiber quality in the care of cotton, the timing and amount of preparation and application of organo-mineral composts.